Garibaldina, an additional promising self-compatible Apulian almond variety - Palasciano M.; Godini A. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Between 1974 and 1990, 29 self-fruitful sweet and bitter almonds have been individuated within the Apulian native germplasm. The essential characteristics of the above cultivars have been presented at the GREMPA meetings of Bari (1977), Salonika (1985) and Nimes (1990). In the present paper the essential traits of cv. Garibaldina, an additional self-fruitful Apulian sweet almond are reported. Garibaldina is grown by time immemorial on the surroundings of Bari and populates an environment where olives is the major crop. Besides self-fruitfulness Garibaldina possesses several traits of horticultural interest, such as medium-late blooming, high and consistent yield, good kernel shape and taste, absence of doubles.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)